The unlikely hero of room 13B - Toten, Teresa, 1955- (New York : Delacorte Press, 2015)
"Adam not only is trying to understand his OCD, while trying to balance his relationship with his divorced parents, but he's also trying to navigate through the issues that teenagers normally face, namely the perils of young love"--
"Originally published in paperback by Doubleday Canada, Toronto, Ontario, in 2013."
Includes bibliographical references (page 289).
Keywords: Obsessive-compulsive disorder -- Juvenile fiction; Schools -- Juvenile fiction; High schools -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Emotional problems of teenagers -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Obsessive-compulsive disorder -- Fiction; Emotional problems -- Fiction; Dating (Social customs) -- Fiction; Family problems -- Fiction; High schools -- Fiction; Schools -- Fiction; Young adult fiction